Metodologia de Verificação Funcional para Circuitos Analógicos - Fonseca, Adauto Luis Tadeo Bernardes da (2009)
This work proposes a new methodology to verify those analog circuits, providing an automated tools to help the verifiers to have a more truthful result. This work presents the development of new methodology for analog circuits verification. The main goal is to provide a more automated verification process to certify analog circuits functional behavior. The proposed methodology is based on the golden model technique. A verification environment based on this methodology was built and results of a study case based on the validation of an operational amplifier design are offered as a confirmation of its effectiveness. The results had shown that the verification process was more truthful because of the automation provided by the tool developed